Evaluation of Osseointegration of Trabecular Titanium Implants Produced of Pontastacus leptodactyluswith Porous Metal Technology: An Experimental Study - Ozcan, Erhan Cahit; Tanrisever, Murat; Aydin, Yildiz; Tekin, Bahar; Sagsoz, Asli; Bozoglan, Alihan; Dundar, Serkan (Univ Zulia, Facultad Ciencias Veterinarias, 2025)
Trabecular titanium (TM) implants produced with porous metal technology are used in dental implant treatments due to their resemblance to cancellous bone and their physical and mechanical properties. The objective of this study was to perform a histological assessment and comparison of the bone-implant contact (BIC) rates between trabecular metal (TM) implants and conventionally machined-surface implants in rat femurThe study was conducted using twenty healthy adult male Sprague-Dawley rats, which were randomly allocated into two equal groups: one serving as the control group and the other receiving trabecular metal (TM) implants. All implants were surgically placed into the right femora of the rats. A curved incision approximately 10-15 mm long was made on the anterolateral aspect of the right knee. The knee joint cap-sule, formed by the femur and tibia, was dissected. Following this procedure, the patella was subluxed, exposing the inter-condylar fossa of the femur for implant placement. Following a 4-week healing period, undecalcified histomorphometric analyses of the samples were performed. BIC (%) measurements were conducted in the histomorphometric evaluations. Group comparisons were analyzed using the Student's t-test. TM implants exhibited an average BIC of 37.13%, while standard cylindrical implants had an average BIC of 29.13%, With a significant statistical difference between the two groups (P < 0.05). Within the limitation of this study titanium implants produced with TM technology have higher percentages of BIC than standard cylindrical titanium implants
Evaluación De La Osteointegración De Implantes Trabeculares De Titanio Fabricados Con Tecnología De Metal Poroso: Un Estudio Experimental
Keywords: Titanium implants; trabecular titanium implant; porous metal; osseointegration; bone implant connection